2000
DOI: 10.1007/s002849910065
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Ruminal Methanogens from Grazing Cattle

Abstract: To obtain information on the diversity of ruminal methanogens in grazing animals, three ruminal methanogens from grazing cattle were characterized and identified. Two of the isolates were rod-shaped, with one staining Gram-positive and being non-motile (BRM9), and the other (BRM16) staining Gram-negative and being motile. These isolates grew only on H(2)/CO(2) and formate, and optimally at 38 degrees C and pH 6.5-7.0. The third isolate (CM1) was non-motile, pseudosarcina-shaped, and grew on H(2)/CO(2), acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 28 publications
3
60
0
5
Order By: Relevance
“…According to some literature data, predominant methanogens in the rumen ecosystem of farm animals include microorganisms of the genus Methanobrevibacter and Methanosaricina, and especially the following species: Methanobacterium formicicum, Methanobrevibacter ruminantium, Methanosaricina barkeri, Methanosaricina mazei -E-mail: adamck@jay.up.poznan.pl and Methanomicrobium mobile (Stewart et al, 1997;St-Pierre and Wright, 2012). Other data demonstrated predominance of only M. ruminantium (Leahy et al, 2010), whereas other data indicated the order Methanobacteriales as predominant in the rumen (Jarvis et al, 2000). However, the literature is still expanding and newer methanogens are being identified (Wright et al, 2008;Zhou et al, 2009;King et al, 2011;Lee et al, 2013).…”
Section: Characteristics Of the Rumen Ecosystem In Relation To Methanmentioning
confidence: 99%
“…According to some literature data, predominant methanogens in the rumen ecosystem of farm animals include microorganisms of the genus Methanobrevibacter and Methanosaricina, and especially the following species: Methanobacterium formicicum, Methanobrevibacter ruminantium, Methanosaricina barkeri, Methanosaricina mazei -E-mail: adamck@jay.up.poznan.pl and Methanomicrobium mobile (Stewart et al, 1997;St-Pierre and Wright, 2012). Other data demonstrated predominance of only M. ruminantium (Leahy et al, 2010), whereas other data indicated the order Methanobacteriales as predominant in the rumen (Jarvis et al, 2000). However, the literature is still expanding and newer methanogens are being identified (Wright et al, 2008;Zhou et al, 2009;King et al, 2011;Lee et al, 2013).…”
Section: Characteristics Of the Rumen Ecosystem In Relation To Methanmentioning
confidence: 99%
“…Proper functioning of the digestive tract of ruminants is closely linked to the abundance and composition of the microbiota in the forestomach, which is a complex ecosystem comprising a vast diversity of bacteria, protozoa and fungi (6). Microorganisms making up the microflora of the rumen, and in particular the interactions between them and physiological processes in the body, directly affect the animal's physical condition and state of health (3,9,17,28). However, our knowledge of the rich diversity of microbial species in the rumen and our 1) Study financed by the General Directorate of the State Forests National Forest Holding in Poland (ZKE-U-6).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…The available literature contains numerous reports on the microbiota of domesticated ruminants and its effect on their well-being (7,17,24,35), but there is very little information on free-living ruminants, particularly with respect to the effect of the type of food consumed on parameters of the forestomach microbiota. Red deer is a species commonly found in Poland (4,13).…”
Section: Effect Of Balanced Supplementary Feeding In Wintermentioning
confidence: 99%
“…Archaeal methanogens are obligate anaerobes (38), and species of the order Methanobacteriales are the most common methanogens found in the rumen (11). Recent studies using culture-independent methods investigating the methanogenic communities in the rumens of sheep and cattle have identified 21 different strains belonging to 13 species in sheep (40,41,43,44) and 13 different strains related to 8 species in cattle (23,37,42).…”
mentioning
confidence: 99%